The leverage ratio is not the problem - Paul H. Kupiec (American Enterprise Institute (AEI), 2017)
Recent proposals have recommended important modifications to the supplemental leverage ratio (SLR) to promote the production of market liquidity and other beneficial banking activities that are alleged to have declined because of the introduction of Basel III capital regulations. A much better solution for promoting liquidity is to significantly raise the minimum SLR to minimize the debt-overhang problem and revise the deposit insurance pricing system so that premiums are much closer to fair market prices for the insurance.
Keywords: A; 330; premiums; Basel Comittee on Banking Supervision